Uniform well-posedness and low Mach number limit to the compressible nematic liquid crystal flows in a bounded domain. (June 2015) - Yang, Xiuhui
Abstract: We prove global-in-time and uniform-in- ϵ of the strong solutions to the 3 D compressible nematic liquid crystal flows in a bounded domain, where ϵ is the Mach number. Consequently, we obtain the strong solution of compressible nematic liquid crystal model that converges to that of incompressible nematic liquid crystal model. This is the first result on the low Mach number limit for compressible nematic liquid crystal flows in 3 D bounded domain. Our proof relies on the dedicated estimates on the solutions and the subtle use of the boundary conditions.